Nonlinear Vibration of Three-Phase Composite Cylindrical Panels Utilizing Reddy’s Higher-Order Shear Deformation Shell Theory - Dat, Dinh Van; Quan, Tran Quoc; Dinh Duc, Nguyen (VNU Journal of Science: Mathematics - Physics, 2025)
This paper presents a comprehensive analytical framework to characterize the nonlinear vibration behavior of a three-phase composite. The cylindrical panels are supported by a Pasternak-type elastic foundation and subjected to combined thermal environment and mechanical loads. A sophisticated mathematical model is formulated basing on Reddy's higher-order theory to precisely capture the complex interactions between elastic foundation. The material properties of a three-phase composite are meticulously determined through analytical expressions that nonlinearly account for the interactions between the constituent materials. The volume fractions of the components in the magneto-electro-elastic face sheets are assumed to be equal. Analytical vibration solutions for the laminated plate are obtained by applying Galerkin method in conjunction with fourth-order Runge-Kutta method. Numerical results are provided to clarify the impact of geometric and material parameters, temperature increase, magnetic and electric potentials and elastic foundations on the vibration behavior of a three-phase composite.